2005
DOI: 10.1002/pros.20183
|View full text |Cite
|
Sign up to set email alerts
|

Alpha2 macroglobulin, a PSA binding protein, is expressed in human prostate stroma

Abstract: We identified alpha(2)-M expression in the human prostate. An increased alpha(2)-M expression appears to be associated with BPH. Considering the unique features of its protein binding and targeting properties, alpha(2)-M expressed in the prostate may play an important role in regulating benign and malignant prostatic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The concentration of ␣ 2 M in the serum ranges from 1 to 5 M (10). It is produced by many tissues, including prostate stroma (9). Patients with prostate cancers often demonstrate ␣ 2 M levels at the lower end of this range, presumably reflecting proteinase-dependent turnover, not a change in synthetic rate (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of ␣ 2 M in the serum ranges from 1 to 5 M (10). It is produced by many tissues, including prostate stroma (9). Patients with prostate cancers often demonstrate ␣ 2 M levels at the lower end of this range, presumably reflecting proteinase-dependent turnover, not a change in synthetic rate (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, little other evidence indicating a direct role for PSA in disease progression. ␣ 2 M is synthesized by many tissues, particularly the liver; however, it is also produced locally in prostate stromal tissue, where it is available to complex with PSA (9). When a proteinase attacks the so-called "bait region," thiol esters in each of the four ␣ 2 M subunits rupture, and the protein undergoes a very large conformational change, exposing receptor recognition sites in each subunit (10).…”
Section: Prostate-specific Antigen (Psa)mentioning
confidence: 99%
“…However, in patients with prostate cancers, levels below 0.7 Amol/L have been reported (19)(20)(21). Prostate cancer cells may produce a 2 M (22), which should increase the pool size of this protein. Prostate cancer cells, however, also produce the proteinase prostate cancer-specific antigen (PSA) and matrix metalloproteinases (23,24), which convert a 2 M to a 2 M* (18).…”
mentioning
confidence: 99%
“…More recently, it's reported that a2M is also involved in the pathogenesis of atherosclerosis (AS) (Larionov et al 2006(Larionov et al , 2007 and plays a crucial role for the immune efficiency during ageing and in age-related diseases (Mocchegiani et al 2006). It was observed that increased expression of a2M is related to the benign prostatic hyperplasia and plays an important role in regulating the benign and malignant prostatic growth (Lin et al 2005). Wager et al demonstrated that the a2M protein level in plasma of healthy subjects correlates with age (Wagner et al 1982).…”
Section: Introductionmentioning
confidence: 96%